PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF POWERPOINT PADA MATERI CUACA DAN MUSIMUNTUK SISWA KELAS IV - Ahmad Fairuz Fuadi; Eka Ramiati; Nurul Fatimah; Anis Hidayati (Smart Education, 2026)
This study aimed to develop an interactive PowerPoint learning media on the topic of weather and seasons for fourth-grade students and to determine its validity, practicality, and effectiveness. The study employed the Research and Development (R&D) method using the ADDIE model. The participants consisted of two expert validators, two fourth-grade teachers, and 14 fourth-grade students at MI Unggulan Ummul Quro. Data were collected through observations, interviews, questionnaires, and learning achievement tests. The results showed that the media achieved an average validation score of 88.28% (valid), while teacher responses reached 84.37%, indicating that the media was practical to use. Students' average scores improved from 56.07 on the pretest to 86.79 on the posttest, with an N-Gain score of 0.71 in the high category. Therefore, the developed interactive PowerPoint learning media is valid, practical, and effective for improving fourth-grade students' learning outcomes on the topic of weather and seasons.